Effcetiveness of CBT and Sex Therapy on Marital Adjustment and Sexual Function among Patient with Premature Ejaculation - Khandelwal, Mahi; Rathore, Sudha (International Journal of Membrane Science and Technology, 2023)
The satisfaction of a good sexual interaction between spouses is one of the most crucial elements in a happy marriage. The research’s purpose was to ascertain the effectiveness combination of CBT and sex therapy (Master & Johnson, 1970) on marital adjustment (MA) and Sexual Function (SF) among patient with Premature ejaculation (PE). good loving attitude toward each other in relationships, and decreases interpersonal discontent. In this view, Author proposed a combination therapy of sex therapy and CBT for sexual dysfunction, such as PE. The tools used were Brief Sexual Function Inventory (self devised) and Marital adjustment scale (MAS) (Locke & Wallace, 1959). Statistical tools used were Descriptive Statistics, Paired sample t test, Analysis of Variance and Post-Hoc Tukey HSD. The pre-intervention mean score of 4 groups was insignificant on MAS and SES. The results of the paired samples t-test were used to assess pre and posttest scores for all the 3 interventions groups. The post-intervention means score of all 4 groups was significantly different over MAS and SF. The post hoc analysis revealed that the mean score differences were most significant in combined therapy of ST and CBT as compared to ST and CBT individually. This paper utilizes psychological therapy and sex therapy can have larger implication on maintaining sexual intimacy among couples and in turn having a long-lasting effect on marital adjustment.